FORAGE PRODUCTION, MORPHOGENESIS AND AGRONOMIC EFFICIENCY IN PANICUM MAXIMUM BRS QUENIA UNDER NITROGEN LEVELS - Martuscello, J. A.; Ribeiro, Y. N.; Braz, T. G. S.; Ferreira, M. R. [UNESP]; Assis, J. A.; Jank, L.; Reis, G. A. (Inst Zootecnia, 2018)
Nitrogen fertilization modifies the morphogen patterns of forage growth. Therefore, studies on the response of newly introduced plants, such as BRS Quenia, to fertilization can contribute greatly with the recommendation of management strategies and more appropriate doses of fertilizer. The objective with this research was to evaluate aboveground and root dry mass production and the morphogenetic and structural characteristics, as well as the agronomic efficiency of nitrogen fertilization in Panicum maximum cv. BRS Quenia, without fertilization and submitted to nitrogen levels (50, 100 and 200 mg/dm(3)). The experiment was conducted in the greenhouse in a completely randomized design whit four replication. Production characteristics and morphogenetic and structural characteristics of the plants were evaluated. The grass BRS Quenia responded to nitrogen fertilization for all characteristics evaluated. Leaf proportions were higher than stem proportions, regardless of nitrogen fertilization. There were larger increases in aboveground mass production than root production. The increase in fertilization implied in a shorter interval between the emergence of leaves of BRS Quenia grass, as well as increased number of tillers per plant. As nitrogen fertilization increases, there is a decrease in fertilizer efficiency. Nitrogen fertilization positively influences forage production in Panicum maximum BRS Quenia plants and, independently of nitrogen dosage, the aboveground mass acts as the main nitrogen drain.
Keywords: Fertilization; leaf; root; stem; tiller